Cognitive deficits and posttraumatic stress disorder in children: A diagnostic dilemma illustrated through a case study. Issue 2 (14th March 2016) - Malarbi, Stephanie; Muscara, Frank; Stargatt, Robyn
ABSTRACT: Studies investigating the neuropsychological functioning of children who experience trauma have predominantly focused on maltreated populations. This article presents a case study that details the longitudinal outcome of a girl who experienced a motor vehicle accident at 5 years of age. It highlights the clinical relevance of research investigating the neuropsychological impact of single-incident trauma on children. It illustrates difficulties clinicians face in discriminating between the effects of developmental delay, traumatic brain injury, attention-deficit/hyperactivity disorder, trauma, and posttraumatic stress symptoms or posttraumatic stress disorder, especially in children with compensable injuries. The state of the current literature is discussed, and directions for future research are provided.